DEVELOPMENT OF MATHEMATICS LEARNING MEDIA FOR DEAF STUDENTS: PRELIMINARY IMPLEMENTATION RESULTS - Hasanah, Aan; Kusumah, Yaya Sukjaya; 'Ulya, Zahratul (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Deaf students’ learning characteristics should be accommodated in their teaching and learning material. This article reported the results from the preliminary implementation of learning media for teaching mathematics to deaf students. The developed media consist of verbal and nonverbal communication, and implementation results suggested that there was students’ preferential difference in responding to a particular type of communication. Further research with large scale samples is still needed to determine the effect of the media in improving deaf students’ mathematics achievement and how preference in a learning mode influences mathematics achievement.